ANALISIS DAN EVALUASI MODEL BISNIS PADA PT. NUSA BHAKTI CEMERLANG DENGAN PENDEKATAN BUSINESS MODEL CANVAS - , BOB ANDREW HUMALA M ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The aims of this study is to analyze and evaluate the business model of PT. Nusa Bhakti Cemerlang. The Nine Building Block of Business Model from business model canvas is choosen as a method to draw a map of business model of PT. Nusa Bhakti Cemerlang so that we could know how the organization run their business. In the evaluation steps SWOT analysis building blocks is used to observe the strength and weakness, also the opportunities and threat that dwell in each of building block of the organization. The result from the evaluation shows us that PT. Nusa Bhakti Cemerlang has a good strength in key partners and key resources building block, and also the company has a unique value proposition but still the company has a weakness that need to get more attention on key activities and customer relationship building block, also the company indeed has a threat in channels building block. A potential opportunity is found at customer segment building block and customer relationship building block that hopefully will bring a positiveresult to revenue streams building block.